PREGNANCY RATE FOLLOWING LUTEAL PHASE SUPPORT IN POLYCYSTIC OVARY WOMEN USING LETROZOLE WITH OR WITHOUT GONADOTROPIN AS OVULATION INDUCTION - Alizzi, Fadia J (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the effect of luteal phase progesterone supplementation on pregnancy rates in anovulatory infertile polycystic ovary women using letrozole with or without gonadotropin as ovulation induction (OI). Method: A prospective randomized clinical study conducted in the infertility clinic - Al-Yarmouk Teaching Hospital, Baghdad/Iraq from June 2016 to January 2018. A total of 149 infertile polycystic ovary women who achieved ovulation using letrozole alone or with gonadotropin as OI protocol enrolled. Accordingly, the study group divided into two: Group A (letrozole group, no=99) and Group B (letrozole gonadotropin group, no=50). After triggering with human Chorionic Gonadotropin, the women in each group were randomly divided into two subgroup women with luteal phase support (LPS) and women without. The primary outcome measure was pregnancy rate. Results: The study shows that pregnancy rate was higher with letrozole group using LPS although the difference did not reach statistical significant (p=0.08). After adjustment of possible confounders; patients receiving letrozole with gonadotropin with LPS had significantly higher successful pregnancy rate. Conclusion: Administration of LPS after OI in infertile polycystic ovarian syndrome women may improve pregnancy rate.